Women’s Political Representation in Feminist Perspectives: Case Study in the Bone Regency People's Representative Council - Helmi Kamal; Agustan Agustan; Muh. Darwis; Nur Adila Fitriah (Sawwa: Jurnal Studi Gender, 2023)
Women and politics are inseparable but intertwined. This study aims to explore the concept and implementation of women's political representation in Bone Regency by using qualitative methods through interviews with DPRD members, institutions, and the community. Although women's participation in political parties has met the 30% quota according to the KPU, women's representation in the Regional Representative Council (DPRD) of Bone Regency is only 4 out of 45 elected members (2019-2024). The analysis shows that the implementation of women's political representation has not been maximized, influenced by structural, cultural, religious stigma, and economic factors. Local regulations do not fully reflect women's needs and rights. Proposed solutions include political education, broad access for women, increasing awareness and confidence, and building political and social networks. This research shows that a concerted effort is needed from relevant parties to improve structures, overcome cultural and religious stigma, and create economic conditions that support women in actively participating in politics.